PEMBINAAN KARAKTER SISWA BERBASIS PENDIDIKAN AGAMA DI SD DAN SMP DIY - Marzuki Marzuki (Jurnal Kependidikan, 2011)
The study is aimed at identifying models of character building of elementary and junior secondary school students based on religious education in the province of Yogyakarta. The study is a research and development (R D) designed in three stages. In the first stage (2010) the study was a survey in 20 elementary and junior secondary schools in Yogyakarta. The data were collected by observation, interviews, focus group discussions, and documentation. The cross-check technique was used for data validity The data were analysed by the inductive analysis technique. The results showed: 1) A special model was not found yet in character building based on religious education in the elementary and junior secondary schools in Yogyakarta. Character building developed in the elementary and junior high schools was still one that was general, 2) A model should be developed for character building in school based on religious education to make religious education as a major base for developing students characters. Religious education should actually teach religious attitudes and behaviors. Another important aspect to be considered in the framework of an effective character building in schools is the vision, mission, and goals for the school, and togetherness. There are programs that are clear and detailed, involving all subjects and all teachers. There are support facilities and special teams for the character building programs